Engaging with clean power: integrated, hands-on lessons on photocatalytic hydrogen production for high school students - Han Fu; Zhenhua Pan; Jill Wenderott (Discover Education)
Abstract As the global demand for science, technology, engineering, and mathematics (STEM) professionals continues to rise, early high school education plays a crucial role in inspiring future innovators and preparing them for scientific challenges. This paper presents an integrated short course for high school students focused on sustainable energy generation technology via photocatalytic hydrogen production. The course is structured into four modules, including theoretical instruction with hands-on experiences in laboratory and outdoor settings. Module 1 introduces the hydrogen economy and the fundamentals of photocatalysis, emphasizing the potential of hydrogen as a clean energy carrier and its critical role in addressing climate change. In Module 2, students conduct laboratory experiments to measure hydrogen production using various photocatalysts, including titania (TiO2), graphitic carbon nitride (g-C3N4), and modified strontium titanate (SrTiO3). Module 3 takes learning outdoors, where students examine the effects of natural sunlight and environmental factors on photocatalytic efficiency, thereby gaining practical understanding of how photocatalysis functions in real-world conditions. Finally, Module 4 facilitates structured discussions, encouraging students to critically analyze the broader societal and technological implications of renewable energy technologies. By integrating theory with practice, this course not only enhances students’ understanding of sustainable energy technologies but also fosters critical thinking, creativity, and problem-solving, empowering them to tackle future challenges in advancing renewable energy solutions and contributing to global sustainability. Graphical Abstract